Nipple aspirate fluid—A liquid biopsy for diagnosing breast health. Issue 9 (26th June 2017) - Shaheed, Sadr‐ul; Tait, Catherine; Kyriacou, Kyriacos; Mullarkey, Joanne; Burrill, Wayne; Patterson, Laurence H.; Linforth, Richard; Salhab, Mohamed; Sutton, Chris W.
Abstract : Purpose: Nipple secretions are protein‐rich and a potential source of breast cancer biomarkers for breast cancer screening. Previous studies of specific proteins have shown limited correlation with clinicopathological features. Our aim, in this pilot study, was to investigate the intra‐ and interpatient protein composition of nipple secretions and the implications for their use as liquid biopsies. Experimental design: Matched pairs of nipple discharge/nipple aspirate fluid (NAF, n = 15) were characterized for physicochemical properties and SDS‐PAGE. Four pairs were selected for semiquantitative proteomic profiling and trypsin‐digested peptides analyzed using 2D‐LC Orbitrap Fusion MS. The resulting data were subject to bioinformatics analysis and statistical evaluation for functional significance. Results: A total of 1990 unique proteins were identified many of which are established cancer‐associated markers. Matched pairs shared the greatest similarity (average Pearson correlation coefficient of 0.94), but significant variations between individuals were observed. Conclusions and clinical relevance: This was the most complete proteomic study of nipple discharge/nipple aspirate fluid to date providing a valuable source for biomarker discovery. The high level of milk proteins in healthy volunteer samples compared to the cancer patients was associated with galactorrhoea. Using matched pairs increased confidence in patient‐specific protein levels but changes relating to cancer stage require investigation of a larger cohort.